Material deprivation affects the management and clinical outcome of hepatocellular carcinoma in a high-resource environment. (November 2021) - Cucchetti, Alessandro; Gramenzi, Annagiulia; Johnson, Philip; Giannini, Edoardo G.; Tovoli, Francesco; Rapaccini, Gian Ludovico; Marra, Fabio; Cabibbo, Giuseppe; Caturelli, Eugenio; Gasbarrini, Antonio; Svegliati-Baroni, Gianluca; Sacco, Rodolfo; et al.
Abstract: Aim: This study investigated how material deprivation in Italy influences the stage of hepatocellular carcinoma (HCC) at diagnosis and the chance of cure. Methods: 4114 patients from the Italian Liver Cancer database consecutively diagnosed with HCC between January 2008 and December 2018 were analysed about severe material deprivation (SMD) rate tertiles of the region of birth and region of managing hospitals, according to the European Statistics on Income and Living Conditions. The main outcomes were HCC diagnosis modalities (during or outside surveillance), treatment adoption and overall survival. Results: In more deprived regions, HCC was more frequently diagnosed during surveillance, while the incidental diagnosis was prevalent in the least deprived. Tumour characteristics did not differ among regions. The proportion of patients undergoing potentially curative treatments progressively decreased as the SMD worsened. Consequently, overall survival was better in less deprived regions. Patients who moved from most deprived to less deprived regions increased their probability of receiving potentially curative treatments by 1.11 times (95% CI 1.03 to 1.19), decreasing their mortality likelihood (hazard ratio 0.78 95% CI 0.67 to 0.90). Conclusions: Socioeconomic status measured through SMD does not seem to influence HCC features at diagnosis but brings a negative effect on the chance of receiving potentially curative treatments. Patient mobility from the most deprived to the less deprived regions increased the access to curative therapies, with the ultimate result of improving survival. Highlights: A Multicentre Italian study on the impact of material deprivation on hepatocellular carcinoma (HCC) outcome. Patients were stratified according to the material deprivation rate of Italian regions. HCC survival was better in less deprived Italian regions. Migration from most to less deprived regions improved HCC survival. Effect of deprivation was mainly because of different access to HCC curative treatments.